PENGARUH KUALITAS PELAYANAN JASA DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA HOTEL PERMATA LAND RANTAUPRAPAT - Pitriyani, Pitriyani, (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2017)
Customer Loyalty is customer commitment toward a registered, services or suppliers(Company), based on a very positive attitude and reflected in the re-purchase consistent.Customer Loyalty can be affected by many factors including the quality of service and price.The object of this research is the Permata Land Rantauprapat Hotel. The purpose of thisresearch is to analyze the influence of service quality and price of customer loyalty in the HotelPrecious Land Rantauprapat . The population in this research is the consumers who stay inHotel Permata Land Rantauprapat . The sample in this research is 98 respondents. The typeof data is the primary. Data collection method using questionnaires. The analysis techniquesused is multiple regression. The results of multiple regression analysis between the quality ofservice to the customer loyalty get the positive results of 0.035 hkd and from the results of thehypothesis test using test - t shows the results of a significant number of 10.532 and sig. 0,003<a = 0.05. The results of multiple regression analysis between the price of consumersatisfaction obtain positive results of 0,734 and from the results of the hypothesis test using test– t shows the results of a significant number of 11.583 and sig. 0,000 <a = 0.05. This can beconcluded that the quality of service and prices have positive and significant impact oncustomer loyalty